Influencia del estilo de liderazgo en la gestión y resolución de conflictos laborales del personal administrativo en la ESPAM-MFL - Chesme Bonilla, María Agustina (2025)
The objective of the research was to analyze the influence of leadership style on the management and resolution of labor conflicts among administrative staff at the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López (ESPAM-MFL). To achieve this, the analytical and synthetic, inductive and deductive methods were used, along with qualitative, quantitative, and field research approaches. The study was carried out in three main phases. In the first phase, a bibliographic review of leadership styles was conducted, while simultaneously, surveys were administered to administrative supervisors to evaluate their perception of how they manage their teams. In the second phase, data were collected regarding the administrative staff's perception of their supervisors, which allowed for the identification of discrepancies and areas for improvement. Finally, in the third phase, an improvement plan was designed, including training proposals and strategies aimed at strengthening key competencies for conflict management and mediation. The results highlighted the need to implement training programs in soft skills, effective communication, and emotional intelligence, in addition to formalizing an internal mediation system to facilitate equitable conflict resolution. The conclusions emphasize the importance of adequately executing the proposed improvement plan to optimize leaders' decision-making and foster a harmonious and productive work environment. This will contribute to both organizational development and the well-being of the staff at ESPAM-MFL.